The Burden of the Broken Grid: Modelling power-sector reliability to support low carbon development in Nigeria - Sarah Golobish; Rudolf Yeganyan; Naomi Tan; Carla Cannone; Mark Howells (Energy Strategy Reviews)
Nigeria has one of the greatest electricity deficits globally and, even in areas connected to the central grid, struggles to provide reliable power across the nation. Frequent system collapses and widespread reliance on diesel generation present a burden for Nigerian households and the economy as a whole. One causal factor in these collapses is capacity inadequacy owing to reduced plant availability as plants are frequently non-operational due to maintenance or other management issues. Using a combination of OSeMOSYS and FlexTool modelling, this study shows the significant burden that persistently unavailable plants present for decarbonisation of the Nigerian energy system. Modelling which includes reliability improvements nearly halves total system costs and emissions versus business-as-usual. Further, Nigeria is unable to meet its 2021 Nationally Determined Contributions (NDCs) without such improvements, indicating that increasing plant availability and reducing diesel generator use must be prioritized in policy to support national implementation of these targets.